Studi Kasus Pelanggaran Etika Bisnis: Kasus Monopoli PT. Perusahaan Listrik Negara - Azzahra, Nadya; Desta Zahwa Aulia; Azizah, Zahrah (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
A business monopoly is when a company controls the trading market without any competitors selling the same goods or services. Business monopoly aims to control the market and create a stable economic flow. This happens because of business monopoly in certain businesses, such as PT PLN, to maintain economic stability and domestic electricity supply, because PLN cannot freely cut and supply electricity supply in the country (Juanda & Ali, 2022). This research aims to identify violations of business ethics in PT PLN's monopolistic practices and their impact on public trust. This research uses a qualitative approach with a case study method to analyze violations of business ethics at PT PLN. The results show that although PT PLN legally has monopoly rights, there are several practices that trigger criticism from the public and supervisory institutions. PLN's monopoly often harms consumers through inadequate services and increases in basic electricity tariffs. This research concludes that PT PLN needs to thoroughly evaluate its compliance system with operational standards in accordance with business ethics.